Find dy⁄dx if y=(2-x)√x?

6 Answers

Relevance
  • 2 years ago

    y = (2 - x)√x

    y'(x) = -(3 x - 2)/(2 sqrt(x))

  • Como
    Lv 7
    2 years ago

    y = (2 - x) x^(1/2)

    dy/dx = (-1) x^(1/2) + (1/2) x^(-1/2) (2 - x)

    dy/dx = (-1/2) x^(-1/2) [ 2 x - (2 - x) ]

    dy/dx = [ 3x - 2 ] / [ 2 x^(1/2) ]

  • 2 years ago

    y = (2 - x)√x

    y = 2√x - x^(3/2)

    dy/dx = 2 * 1/2 * x^(-1/2) - 3/2 * x^(1/2)

    dy/dx = 1/x^(1/2) - 3x^(1/2)/2

  • 2 years ago

    y(x)=u(x).v(x)

    (∂y/∂x)=u(x).∂v+∂u.v(x)

    now

    ∂y=(2-3x)/(2√x)

  • What do you think of the answers? You can sign in to give your opinion on the answer.
  • 2 years ago

    You know you can google "derivative"?

  • khalil
    Lv 7
    2 years ago

    y = uv

    dy/dx = (-1) √x + (1/2√x)(2-x)

    dy/ dx = (2-3x)/2√x

Still have questions? Get answers by asking now.